Examining the Impact of Learning Motivation on Students' Mathematical Ability at SMPN 1 Mejobo, Indonesia - Enta Pebriana; Jayanti putri purwaningrum; Himmatul Ulya (Badan Penerbit STIEPARI Press, 2025)
Learning motivation is a critical factor influencing students' academic achievement, especially in subjects like mathematics, which is often perceived as challenging. Students with high motivation are generally more enthusiastic, engaged, and active in their learning process. They tend to take the initiative in understanding the material and seek additional resources to reinforce their knowledge. On the other hand, students with low motivation are less likely to actively participate, leading to lower engagement and achievement. This study aims to investigate the correlation between students' mathematical aptitude and their motivation to learn, particularly focusing on how motivation influences their performance in mathematics. A quantitative approach using a correlational technique was applied in this study. The sample consisted of 77 seventh-grade students who were selected using simple random sampling. Data were collected through a mathematical aptitude test on algebraic concepts and a questionnaire designed to assess students' learning motivation. The data analysis included normality and linearity tests, followed by Spearman’s correlation analysis to determine the relationship between mathematical aptitude and motivation. The analysis revealed that the data followed a normal distribution and had a linear relationship between the variables. The correlation coefficient was found to be 0.544, with a significance value of 0.000, indicating a moderately strong and statistically significant positive relationship. This suggests that students with higher motivation tend to have better mathematical aptitude. The findings emphasize the crucial role of learning motivation in academic success, especially in mathematics. Motivated students are more likely to achieve higher academic performance. Therefore, it is important for schools and teachers to create a supportive and engaging learning environment that fosters motivation, which can ultimately lead to improved mathematical learning outcomes.